Clinical Significance of Mesenchymal Circulating Tumor Cells in Patients With Oligometastatic Hormone-Sensitive Prostate Cancer Who Underwent Cytoreductive Radical Prostatectomy - Yang, Guanjie; Xie, Jun; Zhang, Shun; Gu, Wenyu; Yuan, Jing; Wang, Ruiliang; Guo, Changcheng; Ye, Lin; Peng, Bo; Yao, Xudong; Yang, Bin (Frontiers in Oncology, 2022)
Purpose: Growing evidence shows that circulating tumor cells (CTCs) become more aggressive after the epithelial-mesenchymal transition (EMT), though the clinical significance of CTCs undergoing EMT in oligometastatic hormone-sensitive prostate cancer (omHSPC) patients has not yet been reported. Accordingly, the aim of this study was to detect the CTC level and investigate the clinical significance of mesenchymal CTCs in omHSPC patients who underwent cytoreductive radical prostatectomy (CRP). Materials and Methods: Blood samples were drawn from 54 omHSPC patients who underwent CRP. The CanPatrol CTC enrichment technique was applied to isolate and identify different phenotypes of CTCs, which were classified as epithelial (E-CTCs), mesenchymal (M-CTCs), or biphenotypic epithelial/mesenchymal (Bi-CTCs). Univariable and multivariable Cox regression analyses were employed to investigate potential prognostic factors for metastatic castration-resistant prostate cancer (mCRPC)-free survival and cancer-specific survival (CSS). The prognostic value of CTCs for CSS and mCRPC-free survival was assessed using time-dependent receiver operating characteristic (ROC) curves and Kaplan–Meier analysis. Results: CTCs were detected in 51 of 54 patients (94%). E-CTC, M-CTC and Bi-CTC detection rates were 56%, 67% and 85%, respectively. A positive correlation was found between the M-CTC count and number of bone metastases (p=0.012). Time-dependent ROC analysis showed that the M-CTC count had higher predictive power than E-CTC or Bi-CTC for mCRPC-free survival (3-year area under the curve [AUC] values: 0.64, 0.60 and 0.61) and CSS (3-year AUC: 0.86, 0.58 and 0.67). Additionally, time-dependent ROC analysis revealed total CTCs (T-CTCs) ≥5 and M-CTCs ≥2 to be the cutoff points with optimal specificity and sensitivity. Based on multivariable Cox regression, T-CTC and M-CTC counts were both independently associated with CSS and mCRPC-free survival (all p <0.05), though E-CTCs and Bi-CTCs had no significant prognostic value (all p >0.05). Patients with T-CTC≥5 or M-CTC≥2 had significantly worse mCRPC-free survival and CSS than those with T-CTC<5 or M-CTC<2 (all p <0.05) after CRP. Conclusion: CTC quantification and phenotype characterization provides prognostic information, and M-CTCs can be used as a novel biomarker for omHSPC patients who undergo CRP. The results need to be validated in prospective studies.